Application of soft material for reclamation fill - Chua, Feng Jun (2014)
Singapore is a city state with limited land space, hence to cope with the growing demands of land use, land reclamation has to be carried out. However, there is severe shortage of granular fill materials (sand) as reclamation fill. On the other hand, a large amount of soft cohesive soil (marine clay) is generated through infrastructure development and maintenance dredging works. The disposal of these excavated spoil and dredged materials becomes a problem in the land-scarce Singapore. These two problems can be overcome if an innovative method can be developed to use these abundant soft materials to replace the acute shortage of granular fill material for land reclamation works. However soft clay is not extensively used in reclamation works due to limited knowledge about its behaviour during the filling and settling process.